Work Family Conflict on Nurses’ Performance at Prevate Hospital in Jakarta - susanti, susanti; Indrawati, Ratna; Purwati, Wahyuni Dian (Alta Dharma Publisher, 2022)
Background. Nurse is one of the professions that has an important role in efforts to maintain the quality of service in hospitals, due to a professional group with the largest number. Objective. The study aimed to analyze the effect of workload and work family conflict on the Nurses’ performance at private hospital in Jakarta with work motivation as an intervening variable. Method: A cross-sectional study with survey approach was applied in this study. Results: The results found that workload has a negative effect on working motivation with estimate score was -0.157, and p-value was 0.035. Work family conflict has a negative effect on nurses’ performance with estimate score was -0.737, and p-value was 0.000. Work Family Conflict was negative effect on nurses’ performance with estimate score was -0.469, and p-value was 0.000. Work motivation has a positive effect on the performance of nurses, this is indicated by the value estimate=0.649, p-values 0.000<0.05. Conclusion: Variables Workload and Work Family Conflict affect the performance of private hospital nurses in Jakarta through work motivation